PENGARUH KUALITAS LAYANAN TERHADAP KEPERCAYAAN DAN NIAT PELANGGAN UNTUK MELAKUKAN TRANSAKSI E-COMMERCE - Sidik Sidik (Paradigma, 2013)
The purpose of this study is to analyze the influence of service quality that consists oftangible, reliability, empaty, responsiveness and assurance webstore on trust (trust) and theintention or interest (intention) customers to conduct e-commerce transactions. Analyzing theinfluence of faith (trust) to an interest or intention (intention) to conduct e-commerce transactions.In this study, took samples of e-commerce users among students at undergraduate andpostgraduate STMIK Nusa Mandiri, who had conducted an e-commerce transactions. The maininstrument of data collection in the form of questionnaires and measured by Likert scale. Thenumber of respondents in this research are 245 respondents. Methods of data analysis used isStructural Equation Model (SEM). Data were analyzed using the software AMOS 7. Results oftesting the structural model does not generate confidence level (probability) or p ≤ 0.05 so thatused path analysis (path anlysis) to determine the causal relationship between variables. Resultsof path analysis test reliability obtained only variable that directly affects the trust and intentionwhile trust among the variables have a direct relationship with intention.Keyword : e-commerce, online shop, trust model, service quality